Investigating the Use of Project-Based Learning in Enhancing Indonesian University Students’ Cultural Knowledge - Lewinna Aguskin; Maryani Maryani (Bina Nusantara University, 2020)
The research investigated the use of email interview to develop the critical thinking and creativity of the university students in American culture classes. The students conducted email interview with Americans for group project and had group discussion with the Americans. Learning culture was an integral part of learning a language, which was crucial for the Englsih as a Foreign Language (EFL) learners to develop their awareness and understanding of the rich and dynamic cultural aspects of the target language. Thus, providing cultural experiences through project-based learning (PBL) would be motivating for the language learners in exploring the target culture. The data were collected from students’ open-ended online questionnaire and observation notes, which contain students’ interview result and their presentation slides. Descriptive statistics and thematic analysis were used in analyzing the data. The findings indicate that the use of project-based approach is helpful to enhance the students’ understanding and critical thinking skills. Moreover, it is found that the students’ positive attitude has increased due to the use of PBL. They are more critical towards the cultural phenomenon since their communication skill has developed.